Efikasi diri dan motivasi belajar dengan stres akademik mahasiswa yang mengerjakan skripsi - Risda Ayu Tsabitah; Nur Hasan (PSYCOMEDIA : Jurnal Psikologi, 2022)
Stress is an individual condition that leads to negative things. Students who are working on their thesis can cause academic stress symptoms because they feel pressured by students because of the gap between the demands of the situation and their abilities. This study aims to determine the relationship between self-efficacy and learning motivation with student academic stress. Participant of this research is student of Faculty of Social Science and Humanities that working on a thesis. Participant of this research is 83 people that collected uses simple random simple random. The data collection using the General Self-Efficacy Scale (GSE), Academic Motivation Scale (AMS) and Perceived Stress Scale (PSS). The data analysis technique used is Sperman's Rho correlation, because there is an assumption test that is not met. The results of the analysis show that there is a negative correlation (r=-0,204) and a significant correlation between self-efficacy and academic stress (p = 0.032; p <0.05) while the results the correlation test between learning concentration and academic stress showed a negative correlation (r=-0.029) but not significant because (p=0.398, p>0.05).